A visualized nomogram to online predict futile recanalization after endovascular thrombectomy in basilar artery occlusion stroke - Lin, ShiTeng; Lin, XinPing; Zhang, Juan; Wan, Meng; Chen, Chen; Jie, Qiong; Wu, YueZhang; Qiu, RunZe; Cui, XiaoLi; Jiang, ChunLian; Zou, JianJun; Zhao, ZhiHong (Frontiers in Neurology, 2022)
Background and Purpose: Futile recanalization occurs in a significant proportion of basilar artery occlusion (BAO) patients after endovascular thrombectomy (EVT). Therefore, our goal was to develop a visualized nomogram model to early identify BAO patients who would be at high risk of futile recanalization, more importantly, to aid neurologists in selecting the most appropriate candidates for EVT. Methods: BAO patients with EVT and a Thrombolysis In Cerebral Infarction scale score of≥2b were included in the National Advanced Stroke Center of Nanjing First Hospital (China) from October 2016 to June 2021. The exclusion criteria were lacking 3-month modified Rankin Scale (mRS), age < 18 years, premorbid mRS score > 2, unavailable baseline CT imaging. Potential predictors were selected for the construction of the nomogram model and the predictive and calibration capabilities of the model were assessed. Results: A total of 84 BAO patients were finally enrolled in this study, and patients with futile recanalization accounted for 50.0% (42). The area under curve (AUC) of the nomogram model was 0.866(95% CL, 0.786-0.946). The mean squared error, an indicator of the calibration ability of our prediction model, was 0.025. A web-based nomogram model for broader and easier access by clinicians is available online at https://trend.shinyapps.io/DynNomapp/. Conclusions: We constructed a visualized nomogram model to accurately and online predict the risk of futile recanalization for BAO patients as well as assist in the selection of appropriate candidates for EVT. Keywords: basilar artery occlusion, futile recanalization, endovascular thrombectomy, nomogram model, predictive model